دورالتكوين في رفع الكفاءة المهنية للأساتذة حديثي التوظيف بجامعة الوادي - فاضل,محمد لمين; كير,زكريا (University of Eloued جامعة الوادي, 2024)
تهدف هاته الدراسة إلى محاولة الكشف عن دور التكوين في الرفع من الكفاءة المهنية للأساتذة حديثي التوظيف بكلية العلوم الإنسانية والاجتماعية -جامعة الوادي-. ولقد تم صياغة فرضيات هذه الدراسة على النحو التالي: الفرضية الرئيسية المتمثلة في: التكوين يسهم في الرفع من مستوى الكفاءة المهنية. والتي جزئت بدورها إلى فرضيات فرعية وهي كالتالي: -التكوين يؤدي الى الرفع من جودة أداء الأستاذ. -التكوين يحسن من المهارات العلائقية للأستاذ. -التكوين يسهم في تحسين المهارات السلوكية للأستاذ. ولكي يتم اختبار الفرضيات المطروحة قمنا بإجراء دراسة ميدانية في كلية العلوم الاجتماعية والإنسانية معتمدين في ذلك على المنهج الوصفي كما اعتمدنا على أداة الاستبيان لجمع المعلومات والتي تضمن 27 عبارة مقسمة على ثلاث محاور وزعت على جميع الأساتذة حديثي التوظيف بالكلية والذي قدر عددهم بحوالي 50 استاذ. وفي الأخير توصلنا إلى النتائج التالية: - التكوين يؤدي الى الرفع من جودة أداء الاستاذ. - التكوين يحسن من المهارات العلائقية للأستاذ. - التكوين يسهم في تحسين المهارات السلوكية للأستاذ. The research problem in this study aims to explore the role of training in enhancing the professional competence of newly hired faculty members at the Faculty of Humanities and Social Sciences, University of El Oued. The hypotheses of this study were formulated as follows: • The main hypothesis: Training contributes to improving the level of professional competence. • This main hypothesis was further divided into the following sub-hypotheses: • Training leads to an improvement in the quality of the professor's performance. • Training enhances the professor's interpersonal skills. • Training contributes to the improvement of the professor's behavioral skills. To test these hypotheses, we conducted a field study at the Faculty of Humanities and Social Sciences, relying on the descriptive method. We used several tools for data collection, including observation and questionnaires, with the questionnaire being the primary tool for gathering information. The questionnaire consisted of 27 statements divided into three sections and was distributed to all newly hired faculty members at the faculty, totaling approximately 50 professors. In conclusion, we arrived at the following results: • Training leads to an improvement in the quality of the teacher's performance
Keywords: التكوين; الكفاءة المهنية; training; professional competence